Sistem Pendukung Keputusan Karyawan Terbaik Metode SAW dan WP Pada PT. Paramount Bed Indonesia - Billy Afri Lorenzia; Achmad Udin Zailani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. Paramount Bed Indonesia was established in 1996 located in West Cikarang, Kab. Bekasi, West Java. In terms of improving the performance of its employees, PT. Paramount Bed Indonesia always gives awards to its best employees in each division once a year. As of now, there are around 3000 employees working. With that many employees, a decision support system is needed that can help the selection of the best employees accurately and quickly. Until now, the employee assessment process is still using manual questionnaire paper and the calculation of the assessment for the best employees is only determined from the total average of all values ​​which makes the calculation look inaccurate and less accurate. Therefore, a web-based decision support system is needed to facilitate the company in assessing and determining the best employees. The implementation of Simple Additive Weighting (SAW) and Weighted Product (WP) is expected to help correct, but does not make decisions to assess them and their role as decision makers. From the results of the calculation of the two methods of Simple Additive Weighting (SAW) and Weighted Product (WP), get the results of a comparison of the two methods. The SAW method obtains better calculation results than the WP method, because the results are more precise and accurate. The best employee selection decision support system uses the Simple Additive Weighting (SAW) and Weighted Product (WP) methods with the development of the Waterfall model, and the notation based on the Unified Modeling Language (UML).